2021
DOI: 10.20524/aog.2021.0677
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence and recent controversies in diverticulitis: a 5-year review

Abstract: Diverticulitis is a common gastrointestinal disease that still garners significant attention and study because of its heterogeneity in presentation and outcome. We provide a review of the newest and most controversial topics in diverticulitis. Recent discoveries on the influence of diet and other environmental risk factors are discussed, showing how the epidemiology of the disease process is shifting away from what was previously felt to be a disorder primarily limited to older western populations. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…This phenomenon might be explained by the fact that some genes, such as LAMB4, TNFSF15, ARHGAP15, ANO1, ELN, and SPINT2, play known roles in processes logically related to diverticulitis, including inflammation, intestinal transport, intestinal motility, and extracellular matrix formation. 59 60 Our study failed to show the effect of other risk factors of colorectal lesions that need further investigation.…”
Section: Discussionmentioning
confidence: 72%
“…This phenomenon might be explained by the fact that some genes, such as LAMB4, TNFSF15, ARHGAP15, ANO1, ELN, and SPINT2, play known roles in processes logically related to diverticulitis, including inflammation, intestinal transport, intestinal motility, and extracellular matrix formation. 59 60 Our study failed to show the effect of other risk factors of colorectal lesions that need further investigation.…”
Section: Discussionmentioning
confidence: 72%
“…29,30 Genetic basis for the disease may also be supported by association between diverticulitis and connective tissue disorders, neuromuscular disorders, and epithelial disorders such as Ehlers-Danlos syndrome, Marfan syndrome, and conditions such as incisional hernias and aortic aneurysms. 31 Laminin protein mutations have been implicated in diverticulitis. Laminins are part of the extracellular matrix and are involved in development of the enteric nervous system.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Laminins are part of the extracellular matrix and are involved in development of the enteric nervous system. 15,31 Diet and lifestyle factors may affect risk of diverticulitis through effects on the intestinal microbiome and chronic inflammation. 15 Finally, environmental effects are thought to contribute to the pathophysiology of diverticulitis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a low-fiber diet in managing diverticulitis remains controversial. Some studies have suggested that it helps in relieving symptoms; however, there is not much evidence to support it [ 39 ]. Studies have advocated using medicines like mesalamine, probiotics, and rifaximin in treating diverticulitis.…”
Section: Reviewmentioning
confidence: 99%